The lung response to ozone is determined by age and is partially dependent on toll-Like receptor 4 - Gabehart, Kelsa (Respir Res, 2015)
BACKGROUND: Ozone pollution has adverse effects on respiratory health in children and adults. This study was carried out in the mouse model to investigate the influence of age and to define the role of toll-like receptor four (TLR4) in the lung response to ozone exposure during postnatal development. METHODS: Female mice (1 to 6 weeks of age) were exposed for 3 h to ozone (1 part per million) or filtered air. Analyses were carried out at six and 24 h after completion of exposure, to assess the effects on lung permeability, airway neutrophilia, expression of antioxidants and chemokines, and mucus production. The role of TLR4 was defined by examining TLR4 expression in the lung during development, and by investigating the response to ozone in tlr4-deficient mice. RESULTS: Metallothionein-1, calcitonin gene-related product, and chemokine C-X-C ligand (CXCL) five were consistent markers induced by ozone throughout development. Compared with adults, neonates expressed lower levels of pulmonary TLR4 and responded with increased mucus production, and developed an attenuated response to ozone characterized by reduced albumin leakage and neutrophil influx into the airways, and lower expression of CXCL1 and CXCL2 chemokines. Examination of the responses in tlr4-deficient mice indicated that ozone-mediated airway neutrophilia, but not albumin leakage or mucus production were dependent on TLR4. CONCLUSIONS: Collectively, the data demonstrate that the response to ozone is determined by age and is partially dependent on TLR4 signaling. The reduced responsiveness of the neonatal lung to ozone may be due at least in part to insufficient pulmonary TLR4 expression. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12931-015-0279-2) contains supplementary material, which is available to authorized users.